Conscious shopping of middle-class consumers during the pandemic: Exploratory study in Mexico, Nigeria, Poland, and Sri Lanka - Anna Maria Nikodemska-Wołowik; Dagmara Wach; Katarzyna Andruszkiewicz; Ade Otukoya (International Journal of Management and Economics, 2021)
This study aims to identify middle-class consumers' habits in four countries during the pandemic of 2020, with special attention to analogous consumers' reactions to extraordinary circumstances during the recession of 2008. Furthermore, this study tried to detect the impact of the pandemic on conscious shopping. Although the consequences of the ongoing pandemic were unforeseeable, the paper opened new avenues for further research on factors responsible for conscious consumption during the unprecedented externality and its significance on the middle-class consumers in culturally diverse markets. To achieve the aforementioned goals, between June and December 2020, computer-assisted web interviews (CAWI) based on pilot stage research were conducted to answer the following questions: How did the pandemic influence the buyers' shopping habits in terms of conscious consumption? What were the reasons for the changes in shopping habits? What kind of consumer behaviors would middle-class buyers recommend to others? One general conclusion, inter alia, should be stressed remarkably: during the pandemic, irrespective of the cultural differences, the middle-class consumers' behaviors did not vary significantly with regards to most of the investigated variables.
Keywords: D9; D12; I12; 650; Consumers; Mexico; Nigeria; pandemic; Poland; Sri Lanka